The Loneliness of a Solitary Dissertation Writer: Avoiding Isolation through a Writing Community - Heh Youn Shin; Carol Rogers-Shaw; COLLEEN UNROE; Xiaoqiao Zhang (Adult Education Research Conference, 2019)
The purpose of this literature review is to examine how various elements of writing groups, collaboration, and peer mentoring help doctoral students overcome obstacles and complete the dissertation process.
Keywords: doctoral study; dissertation writing; collaboration; writing groups; peer mentoring